(untitled) (CIPEEX, 2025)
Diabetes mellitus (DM) is one of the chronic noncommunicable diseases (NCDs) characterized by high blood glucose levels resulting from insulin inefficiency in tissues or insufficient insulin production by the pancreas, affecting approximately 13 million people in Brazil. The 2023 Surveillance of Risk and Protective Factors for Chronic Diseases (Vigitel) indicates that 10.1% of the adult population has diabetes, causing negative impacts on the physical and economic health of citizens, with estimated costs of R 27 billion by 2030. The objective of the study was to analyze diabetes, addressing its causes, complications, and forms of treatment, with an emphasis on prevention and control of the disease. The methodology used for this study was an integrative literature review, with analysis of scientific articles published in the PubMed, SciELO, and Ministry of Health databases, with publications from 2020 to 2025. The results and discussion show that diabetes mellitus is one of the main causes of serious complications, such as cardiovascular disease, kidney failure, retinopathy and neuropathy, and amputations, highlighting the urgency of early diagnosis. Diabetes is divided into three main types: type 2 diabetes, the most common, when the body develops insulin resistance; type 1, when the pancreas cannot produce enough insulin; and gestational diabetes, which appears during pregnancy, increasing a woman’s risk of developing type 2 diabetes after delivery. Diabetes has multiple causes, including both environmental factors linked to the disease and genetic factors, which vary depending on the specific type of diabetes. The most prominent symptoms are constant hunger and thirst, frequent urination, blurred vision, fatigue, or extreme tiredness, among others. Diabetes mellitus is diagnosed through blood tests that measure glucose (sugar) in the body, primarily fasting blood glucose, the oral glucose tolerance test (OGTT), and glycated hemoglobin (HbA1c). Therefore, starting in July 2024, the Brazilian Diabetes Society (SBD) included the 1-hour oral glucose tolerance test in the diabetes mellitus diagnostic algorithm. Treatment involves patients with Type 1 diabetes who require daily insulin injections to maintain blood glucose levels within normal limits. For those with Type 2 diabetes, treatment involves metformin monotherapy or other medications to prevent complications. However, treatment goes beyond pharmacological use; prevention strategies such as physical activity, a healthy diet, and cognitive-behavioral therapy are important for maintaining normal blood glucose levels, as they improve insulin sensitivity and help regulate blood glucose levels. Advanced therapies, such as SGLT2 inhibitors and GLP-1 receptor agonists, complement these treatments. It is concluded that diabetes is a complex disease that requires treatment that not only seeks glycemic control but also the prevention and management of associated risk factors. Accurate diagnosis is essential for understanding the prognosis and choosing the appropriate treatment.